Legal Policy for Management of Criminal Action of Narcotics in Low Education - Bayu Dwa Anugrah; Aryani Witasari (Law Development Journal, 2021)
The objectives of this research are: To know and analyze how legal handling of narcotics crime among low education.To find out and analyze obstacles and solutions prevention of narcotics crime among low education. The results of this study areWays to Overcome the Law on Narcotics Crime Among Low Education, among others: 1) Preventive, namely policies that see the root causes of the main causes of crime through a social approach, a situational approach and a community approach to eliminate the elements of potential interference (Correlative Criminogen Factors); 2) Preventive (prevention), namely to form a society that has resistance and immunity to drugs. Prevention is better than eradication .; and 3) Repressive (repression), namely taking action against and eradicating drug abuse through legal channels and based on law, which is carried out by law enforcers or security forces assisted by the community. Internal obstacles are the lack of resources for sophisticated technology equipment to match the technological sophistication of drug network syndicates in distributing and producing drugs, while external obstacles that come from outside are the confusion of articles in the Narcotics Law regarding sanctions against victims of abusers, lack of participation and public participation as police intelligence to provide information and information in order to uncover and uncover cases of illicit traffic and narcotics abuse. Future efforts will be made to overcome obstacles in overcoming narcotics crime among low education. Drug Crime Unit personnel are given education or training on the use of technology so that they can use IT tools in order to detect narcotics offenders and networks; Narcotics Crime Unit personnel carry out vocational education in the field of combating narcotics crime. And the personnel of the Narcotics Crime Unit are required for investigators to continue their education to higher education so that their insight and understanding of the Narcotics Law can better understand so that they can carry out investigations into a more organized modus operandi.